Adaptive response under multiple stress exposure in fish: From the molecular to individual level. (December 2017) - Gandar, Allison; Laffaille, Pascal; Canlet, Cécile; Tremblay-Franco, Marie; Gautier, Roselyne; Perrault, Annie; Gress, Laure; Mormède, Pierre; Tapie, Nathalie; Budzinski, Hélène; Jean, Séverine
Abstract: Aquatic systems are subjected to various sources of stress due to global changes, such as increasing temperature and pollution. A major challenge for the next decade will be to evaluate the combined effects of these multiple stressors on organisms and ecosystems. For organisms submitted to chemical, biological or physical stressors, the capacity to set up an efficient adaptive response is a fundamental prerequisite for their long-term survival and performance. In this study, goldfish ( Carassius auratus ) were subjected to individual and combined pesticide mixtures and increased temperatures to evaluate their adaptive response in multistress conditions from the molecular to the individual level. Fish were exposed for 16 days to a mixture of pesticides at environmental relevant concentrations (S-metolachlor, isoproturon, linuron, atrazine-desethyl, aclonifen, pendimethalin and tebuconazole) and at two temperatures (22 °C and 32 °C). Three major physiological traits of the stress response were measured: the hormonal response (i.e. plasma cortisol), the metabolic balance from molecular to individuals' levels (metabolomics, cellular energy allocation, energy reserves and global condition indexes), and the cellular defense system induction (SOD, CAT and GST). Results show that (1) environmentally relevant concentrations of pesticides lead to significant responses in fish at all biological levels; (2) the metabolic response depends on the nature of stress (thermal vs. chemical); and (3) fish may be unable to set up an efficient adaptive response when chemical and thermal stresses were combined, with adverse outcomes at the individuals' level. Highlights: Goldfish were exposed to a pesticide mixture and elevated temperatures for 16 days. Metabolomics and biochemical approaches were conducted. Adapted and coordinated early responses to individual stressors were observed. Multistress reduced earlier endocrine response, antioxidant defense and metabolic compensation.